Magnified - Pratt, Minnie Bruce (Book collections on Project MUSE., 2021)
"Chronicling one year in the life of a queer couple facing life-threatening illness, this sequence of poems explore what words can do to hold off loss and death while living on in a world of injustice and sorrow"--